Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique